Ethnographic study of intergenerational relationships involved in domestic health care during pregnancy and puerperium (Molinos, Salta, Argentina) - Morgante, María Gabriela (2018)
In this paper we analyze intergenerational relationships in the care of women and children during pregnancy, childbirth, and puerperium in Molinos (Salta). Our study is ethnographic and qualitative, focusing on the stories of women from different generations who primarily assume responsibilities and tasks related to domestic care. We compare their domestic and extra-domestic relationships and experiences in order to assess whether they correspond to the cross-age integration model. We find that generational differences in the participation of elderly women in care arise from the changing composition and location of households, conjugal relationships, subsistence activities, and access to health institutions. Despite these differences, older women still provide care and social support during these life stages and become references for decision-making.